SPECROPHOTOMETRIC ESTIMATION AND STATISTICAL CORRELATION FOR ROSIGLITAZONE IN RAT AND HUMAN PLASMA - Adhikari, Lopamudra; Mishra, Uma Shankar; Murthy, P.N (Asian Journal of Pharmaceutical and Clinical Research, 2013)
ABSTRACT Â Objective: A rapid and sensitive Spectrophotometric method was developed for Rosiglitazone in rat and human plasma. Method: The sample was prepared by simple extraction method without derivatization and no use of buffer .Methanol and acetonitrile were used as the solvents in the proposed methods. Results: Calibration range extended for rosiglitazone from1mcg/ml to 10 mcg/ml in rat plasma and 1mcg/ml to 17mcg/ml in human plasma with good regression coefficients in both the cases. The Limit of Detection and Limit of Quantification were found out to be 0.726mcg/ml and 2.2mcg/ml in rat plasma and 0.414mcg/ml and 1.255mcg/ml in human plasma. Assay results from the proposed method were found to be 100.2% and 100.12% in rat and human plasma respectively. Stability of the drug in both the plasma was found to be suitable in both refrigerated and ambient conditions. Conclusion: The current method implied no significance difference as for estimation in rat and human plasma as tested from ANOVA analysis and can be extended pharmacokinetic studies. The proposed method was found prudent to be used in routine QC analysis. Keywords: Rosiglitazone, UV-Vis Spectrophotometer, Rat Plasma, Human Plasma, Statistical Correlation